2017
DOI: 10.4274/tjo.32448
|View full text |Cite
|
Sign up to set email alerts
|

Eye Injuries from Pencil Lead: Three Cases

Abstract: Corneal stromal and/or penetrating ocular injuries from pencils and pencil lead are more common in childhood and may lead to intraocular infection or severe intraocular sterile inflammatory reaction. Herein we report 3 children with ocular trauma due to pencil lead injuries. The first case had corneal stromal injury caused by a pencil. In the second case, a pencil perforated the cornea and contacted the iris. In the third case, pencil lead perforated both the cornea and iris and reached the vitreous through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…Nevertheless, most surgeons approve of surgical removal of a foreign body because it is an origin of life-threatening hemorrhage and infectious complications. 1 , 11 , 14 , 15 In our case, there was a high risk of injury to the ICA if the foreign body had been pulled out from the outside because of its close proximity to this artery. It may be safer to remove such foreign bodies under visual monitoring.…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, most surgeons approve of surgical removal of a foreign body because it is an origin of life-threatening hemorrhage and infectious complications. 1 , 11 , 14 , 15 In our case, there was a high risk of injury to the ICA if the foreign body had been pulled out from the outside because of its close proximity to this artery. It may be safer to remove such foreign bodies under visual monitoring.…”
Section: Discussionmentioning
confidence: 61%
“…Fakat, endoftalmi benzeri ciddi inflamatuar reaksiyon gösteren hastalar literatürde mevcuttur, ancak bu tablonun kurşun kalemlerdeki hangi bileşenden kaynaklandığı konusunda fikir birliği oluşturulamamıştır. 4,6,7 Honda ve ark., kurşun kalem yaralanması ile başvuran ve periferik retinasında grafit yabancı cisimciği saptanan 5 yaşındaki çocuk hastayı, 6 yıl boyunca fundus fotoğrafları, fundus fluoresein anjiyografi ve seri elektroretinogram ile takip ettiklerini ve yabancı cisime bağlı herhangi bir toksisite ve hasar izlemediklerini bildirmişlerdir. 4 Arıcı ve ark., 15 yaşında sağ gözüne kurşun kalem battıktan 2 gün sonra başvuran hastalarında kornea temporalinde limbusa yakın yerleşimli, kornea ve irisi penetre eden kurşun kalem ucu saptamışlardır.…”
Section: Discussionunclassified
“…Hastanın göz içi yabancı cismi çıkarıldıktan sonra, ön kamaraya 2 mg/0,05 mL triamsinolon ve 0,25 mg/0,05 mL moksifloksasin enjekte ettiklerini, ameliyat sonrası topikal moksifloksasin ve deksametazon kullandıklarını ve bir yıllık takiplerinde ön kamarada reaksiyon izlemediklerini bildirmişlerdir. 6 Amritanand ve ark., 4 ay önce gözüne kurşun kalem travması tarifleyen 6 yaşındaki hastalarının biyomikroskobik ön segment muayenesinde, alt yarıda kornea içerisinde ön kamaraya uzanımı olan kurşun kalem ucu saptamışlar ve iris üzerinde grafit partiküllerinin olduğunu, fakat herhangi bir inflamatuar reaksiyon gelişmediğini bildirmişlerdir. Yabancı cismin çıkartılması ve ön kamaradan karbon partiküllerinin temizlenmesi sonrasında topikal steroid ve siklopentolat kullandıklarını, hastanın izlemlerinde intraoküler enfeksiyon ve toksisite bulgusu saptanmadığını bildirmişlerdir.…”
Section: Discussionunclassified
“…The toxicity of the other components, however, is controversial [7,8]. Arici et al [8] concluded that carbon particles in the cornea are well tolerated in the long run, and that anti-inflammatory medication, preventive antibiotic therapy, and monitoring can help patients with intraocular pencil lead injury have a good prognosis. However, pencil injuries have also been reported to cause severe endophthalmitis [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, with subjects aged 6 months to 81 years, Jack-Okereke et al [4], reported that 6% of all domestic injuries in Enugu is due to pencils/pens injuries. Majority of injuries from pencil and pen in children occur accidentally while writing, drawing, painting or playing with these writing materials either as a stab/poke injury or missile injury [8,10,12]. The child may also trip and fall on a pencil held in the hand [13,14].…”
Section: Introductionmentioning
confidence: 99%